VORTEX LIFTING AND TRANSPORTATION SYSTEM - L. V. Mihnenkov (Научный вестник МГТУ ГА)
The results of numerical research of lifting and transport system of aircraft vertical takeoff and landing, based on the use of the Magnus effect are presented. The formulas for determining its lift and thrust are obtained. The method of engineering calculation of the basic elements of the system based on the data of experimental aerodynamic tests is developed.